Subiektywne sensy i znaczenia doświadczeń zaufania osób z niepełnosprawnością intelektualną - Kaliszewska, Karolina; Żółkowska, Teresa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The presented text is an attempt to answer the question: what senses and meanings are given by people with moderate intellectual disabilities to their experiences of the foundations of trust. The empirical material obtained from conducting qualitative research interviews (unstructured, in-depth) with adults with a moderate degree of intellectual disability revealed that the basis of trust understood as a relationship with other people is everyday knowledge manifested in aspects of knowledge about the essence of trust and knowledge about oneself. The theoretical and empirical assumptions used in the article are based on the interpretative-constructivist paradigm and the phenomenological-hermeneutic perspective.
Keywords: niepełnosprawność intelektualna; subiektywne sensy i znaczenia doświadczeń zaufania; wiedza codzienna; teoria społeczna Alfreda Schütza; paradygmat interpretatywno-konstruktywistyczny; perspektywa fenomenologiczno-hermeneutyczna; intellectual disability; subjective senses and meanings of trust experiences; everyday knowledge; Alfred Schütz`s social theory; interpretative-constructivist paradigm; phenomenological-hermeneutic perspective